Rethinking childhood II: child and space (Morepress Books, 2026)
The collection of papers Rethinking Childhood II / Child and Space continues an exploration of childhood already initiated, but this time approached from a practical perspective–one that observes the child and space within a real-world context. At the very beginning of the volume, readers will find keynote contributions by renowned scholars in their respective fields: Roberta Mineo, who examines the role of environment and space in the Reggio Emilia approach through the lens of group-analytic interpretation; Irena Klasnić, who positions the child and space within the framework of pedagogical discourse; and finally, László Varga, who explores the neuropedagogy of early childhood as an “open window” to the world. The remaining papers in the collection are categorised as professional papers which offer a broad thematic spectrum that connects educational spaces with the wider social community, highlighting the creative educational potential of everyday environments. The works also explore spatiality in relation to children’s musical play in the preschool years, the use of Orff instruments as both stimulus and medium for musical development, as well as visual art activities connected to foreign language acquisition. Furthermore, space is considered in the context of encouraging physical activity within the educational process, viewed as a key factor in the holistic development of the child–with the importance of outdoor play being also emphasised (particularly through the mosaic approach) as an essential counterbalance in today’s digital age. Of particular interest is a contribution addressing the contemporary issue of the socalled “sharenting”, which refers to the increasing tendency of parents to expose their children to media spaces. Several articles explore the relationship between fine motor skills and speech development in toddlers, as well as the child’s perception of the educational environment. Given the thematic scope of the collection–which is firmly rooted in real-world settings and professional practice–we believe this volume will prove valuable to educators, students of early childhood education, other professionals, and the general public alike.